2020
DOI: 10.2147/opth.s269508
|View full text |Cite
|
Sign up to set email alerts
|

<p>Short-Term Efficacy of Selective Laser Trabeculoplasty in Omani Eyes with Glaucoma: A Single Institutional Study</p>

Abstract: Purpose There is some evidence suggesting a different nature of response to selective laser trabeculoplasty (SLT) among different races. Therefore, we aimed to assess the short-term efficacy, safety and nature of outcome of SLT in Omani eyes. Patients and Methods A retrospective review was performed of patients with open-angle glaucoma (OAG) or ocular hypertension (OHTN) who underwent a single session of 360-degree SLT between January 1, 2017 and December 31, 2018. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
1
5
0
3
Order By: Relevance
“…Results from our study showed a reduction of IOP 20-22% from baseline, similar to other studies [7,8]. A single SLT treatment was found to reduce the need for antiglaucoma medications at 36 months and a lower reduction of IOP at two months [9].…”
Section: Discussionsupporting
confidence: 87%
“…Results from our study showed a reduction of IOP 20-22% from baseline, similar to other studies [7,8]. A single SLT treatment was found to reduce the need for antiglaucoma medications at 36 months and a lower reduction of IOP at two months [9].…”
Section: Discussionsupporting
confidence: 87%
“…Al-Busaidi and colleagues examined the short-term efficacy of SLT in OAG and OHT in Omani patients. The mean total energy was 64.03 mJ, which is significantly lower than that reported by Shibata and colleagues, whereas the success rates were significantly higher (51.5% at 5 wk and 72.7% at 12 wk vs. 46% and 29% in the 360-degree SLT group, at 1 and 2 y, respectively) 50,51. Although the definitions of success in both studies were similar, differences in their follow-up periods may account for their different results, as in most studies the IOP-reducing effect of SLT is found to wane with time.…”
Section: Resultsmentioning
confidence: 63%
“…The mean total energy was 64.03 mJ, which is significantly lower than that reported by Shibata and colleagues, whereas the success rates were significantly higher (51.5% at 5 wk and 72.7% at 12 wk vs. 46% and 29% in the 360-degree SLT group, at 1 and 2 y, respectively). 50 , 51 Although the definitions of success in both studies were similar, differences in their follow-up periods may account for their different results, as in most studies the IOP-reducing effect of SLT is found to wane with time. Lai et al 52 reported a 32.1% reduction in IOP, after 5 years of follow-up, in 32 OAG and OHT Chinese patients who underwent SLT at a mean total energy of 73.6 mJ.…”
Section: Resultsmentioning
confidence: 99%
“…Nuestro estudio demostró una reducción estadísticamente significativa de los valores de PIO, tanto a los 6 como a los 12 meses, alcanzando reducciones promedio de un 13 y un 15% respectivamente (p < 0.0001 y p < 0.0002). Estas reducciones estarían dentro de los valores publicados en un reciente metaanálisis, en donde se describen series con descensos que van desde un 6.9 a un 35% a los 12 o más meses de seguimiento [7][8][9][10][11] .…”
Section: Discussionunclassified
“…Por otro lado, la tasa de éxito alcanzada a los 6 y 12 meses de un 46% es discretamente más baja que las series publicadas, en las que se describen rangos de éxito variables desde un 66 a un 75% a los 6 meses y de un 58 a un 94% a los 12 meses [10][11][12] . De los pacientes que obtuvieron éxito en la terapia, el 35 y el 47% de los pacientes no utilizaba fármacos a los 6 y 12 meses respectivamente.…”
Section: Discussionunclassified